Analysis of the Evolution Evidence of Neandertals and Homo sapiens in Apidima Cave - Wu, Haoye (Transactions on Social Science, Education and Humanities Research, 2023)
Apidima Cave, which was first discovered by Theodore Pitsios and his team in the 1970s, is an archaeological site of great importance in the history of anthropology, and many fossils and artifacts were discovered. The most famous of these finds are the two skulls Apidima1 and Apidima2. These skulls have been identified as early members of the Homo sapiens family tree and are among the earliest known fossils of our species in Europe. All the caves were filled with geological sediments during the Middle and Late Pleistocene indicates that the area was a popular location for early humans to inhabit. The site’s complex stratigraphic sequence, spanning the Middle and Upper Paleolithic periods, has allowed researchers to study the evolution of early humans over a long period of time. The cranial and occipital features of Apidima1 illustrate the evolution of the human brain in response to environmental adaptation. The large orbits and prognathic face of Apidima2 illustrate the natural selection of Neanderthals for adaptation to cold environments. The tools and artifacts found in archaeological sites can provide valuable insights into the social structure and daily lives of ancestors.